Pengaruh Pemberian Pupuk ZPT Auksin dan Kompos Kulit Pisang Terhadap Pertumbuhan Bayam Merah (Amaranthus tricolor L.) - Festiarni Indah Sari Hia; Ida Zulfida; Edison Sibagariang (UNIVERSITAS LABUHANBATU, 2023)
Banana peels that are not properly managed will cause environmental pollution. The waste still contains high water content and thus contains organic matter in the form of carbohydrates, proteins and fats. To manage the industry, we can turn it into compost with a mixture of M4 as a decomposer.This study aims to produce compost with banana peel and Zpt auxin on the growth of red spinach (Amaranthus tricolor L.). The research design used in the study was a group randomized design (RAK) with 2 factors and 3 levels of treatment.Factor I there is a dose of banana peel consisting of 3 levels, namely banana peel compost with a total of 27 kg of compostP0 = No treatment (control), P1 = 175 grams / plant, 2.5 tons /ha (equivalent to 10 polybags / plant), P2 = 350 grams / plant 5 tons /ha (equivalent to 15 polybags / plant). While the second factor A0 = no treatment, A1 = 250 ml/liter of water (per polybag), A2 = 500 ml/liter of water (per polybag). Thus obtaining 9 combinations. The research parameters were seen from plant height (cm), number of leaves (strands) sample plant production (g), wet weight, root length (cm) and root volume (ml). The provision of banana peel compost and Zpt auxin has a significant effect on plant height, number of leaves, and wet weight.